COMPUTER SIMULATION OF A DIESEL SPRAY IGNITION AND COMMON RAIL ACCUMULATOR FUEL-INJECTION SYSTEM - Praunseis, Zdravko; Marčič, Simon; Avsec , Jurij; Marčič, Milan (Journal of Energy Technology, 2024)
This paper describes a diesel fuel injection process and a diesel spray formation. A computer simulation of the common rail accumulator fuel-injection system and diesel spray were carried out. The computer simulation enables the observation of the phenomena from rail pressure, which is input data for the calculation of injection parameters, to self-ignition in the diesel combustion chamber. With computer simulation, the pressure values in specific sections of the injection nozzle may be computed, as well as the needle lift, injection rate and total injected fuel. The injection rate is input data for the simulation of the spray. The spray is divided into small elementary volumes in which the amount of fuel and fuel vapour, air, mean, maximum and minimum fuel droplet diameter as well as their number are calculated. In each elementary volume, the total air-fuel ratio and air-fuel vapour ratio are calculated. a new criterion for determining the self-ignition nuclei is described in the paper, based on assumptions that the strongest self-ignition probability lies in those elementary volumes containing the stoichiometric air ratio, where the fuel is evaporated or the fuel droplet diameter is equal to or lower than 0.0065 mm. The most efficient combustion with regard to the consumption and emission will be in that elementary volume containing the stoichiometric air ratio and the fuel droplets with the lowest mean diameters. The injection and combustion parametermeasurements were made in an optically accessible transparent engine. The engine is a single- cylinder transparent engine based on the AUDI V6 engine, equipped with a Bosch Common Rail Injection system. The optical part of the experimental set-up contains two different lasers, while the camera system allows the simultaneous detection of the Mie scattering of the injected fuel, the laser-induced fluorescence of fuel and vapour, the premixed combustion mode and the diffusion mode. A comparison of the computed points with the highest self-ignition probability and the measured points where self-ignition occurred showed good matching.